Human resource information systems - Kavanagh, Michael J.; Johnson, Richard David (Thousand Oaks, California SAGE Publications, Inc., 2018)
"Human Resource Information Systems, edited by Michael J. Kavanagh and Richard D. Johnson, is a one-of-a-kind book that provides a thorough introduction to the field of Human Resource Information Systems (HRIS) and shows how organizations today can leverage HRIS to make better people decisions and manage talent more effectively. Unlike other texts that overwhelm students with technical information and jargon, this revised Fourth Edition offers a balanced approach in dealing with HR issues and IT/IS issues by drawing from experts in both areas. Numerous examples, best practices, discussion questions, and case studies make this the most student-friendly and current text on the market. New to this edition: a new chapter on social media explores how organizations can use social networks to recruit and select the best candidates, a new HRIS Expert feature spotlights real-world practitioners who share best practices and insights into how chapter concepts affect HR professions and New and expanded coverage of key trends such as information security, privacy, cloud computing, talent management software, and HR analytics is included." -- Amazon
PART I: HUMAN RESOURCE INFORMATION SYSTEMS (HRIS): THE BACKBONE OF MODERN HR: Chapter 1. A Brief History and Overview of Technology in HR -- Chapter 2. Database Concepts and Applications in HRIS -- Chapter 3. Systems Considerations in the Design of an HRIS: Planning for Implementations.

PART II: MANAGING HRIS IMPLEMENTATIONS: Chapter 4. The Systems Development Life Cycle and HRIS Needs Analysis -- Chapter 5. System Design and Acquisition -- Chapter 6. Project Management, Change Management, and HRIS Implementation -- Chapter 7. Cost Justifying HRIS Investments.

PART III: ELECTRONIC HUMAN RESOURCE MANAGEMENT (eHRM): Chapter 8. HR Administration and HRIS -- Chapter 9. Talent Management -- Chapter 10. Recruitment and Selection in an Internet Context -- Chapter 11. Training and Development: Issues and HRIS Applications -- Chapter 12. Performance Management, Compensation, Benefits, Payroll, and the HRIS.

PART IV. ADVANCED HRIS APPLICATION AND FUTURE TRENDS: Chapter 13. HRIS and International HRM -- Chapter 14. HR Metrics and Workforce Analytics -- Chapter 15. HRIS Privacy and Security -- Chapter 16. HRIS and Social Media -- Chapter 17. The Future of HRIS: Emerging Trends in HRM and IT.
"Basics, applications, and future directions"--Cover.
International student edition.
Includes bibliographical references (pages 497-527) and indexes.
Keywords: Personnel management -- Information technology; Personnel management -- Data processing